Variation in the Level of eGFR at Dialysis Initiation across Dialysis Facilities and Geographic Regions - Sood, Manish M. (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: The relative influence of facilities and regions on the timing of dialysis initiation remains unknown. The purpose of the study is to determine the variation in eGFR at dialysis initiation across dialysis facilities and geographic regions in Canada after accounting for patient-level factors (case mix). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In total, 33,263 dialysis patients with an eGFR measure at dialysis initiation between January of 2001 and December of 2010 representing 63 dialysis facilities and 14 geographic regions were included in the study. Multilevel models and intraclass correlation coefficients were used to evaluate the variation in timing of dialysis initiation by eGFR at the patient, facility, and geographic levels. RESULTS: The proportion initiating dialysis with an eGFR≥10.5 ml/min per 1.73 m(2) was 35.3%, varying from 20.1% to 57.2% across geographic regions and from 10% to 67% across facilities. In an unadjusted, intercept-only linear model, 90.7%, 6.6%, and 2.7% of the explained variability were attributable to patient, facility, and geography, respectively. After adjustment for patient and facility factors, 96.9% of the explained variability was attributable to patient case mix, 3.1% was attributable to the facility, and 0.0% was attributable to the geographic region. These findings were consistent when the eGFR was categorized as a binary variable (≥10.5 ml/min per 1.73 m(2)) or in an analysis limited to patients with >3 months of predialysis care. CONCLUSIONS: Patient characteristics accounted for the majority of the explained variation regarding the eGFR at the initiation of dialysis. There was a small amount of variation at the facility level and no variation among geographic regions that was independent of patient- and facility-level factors.